Analysis Of Various Translation Techniques In The Book Translation Of Matan Tuhfatul Athfal - Gandari, Amanda Marwah (Nurul Jadid University, 2024)
In the context of Islamic education in Indonesia, classical Arabic texts are commonly used as reference materials, yet their complexity often requires careful translation to ensure accessibility for learners. This study aims to examine the translation techniques applied in the Indonesian version of Matan Tuhfatul Athfal, specifically in the section discussing the rules of Nun Sukun and Tanwin in tajwid. Using a qualitative descriptive design, this research employs documentation-based data collection and applies the Miles and Huberman model for data analysis, including data reduction, display, verification, and conclusion drawing. The findings reveal the use of eight translation techniques by the translator: pure borrowing, literal translation, reduction, transposition, calque, amplification, adaptation, and modulation. These techniques reflect a dynamic approach that balances terminological fidelity with pedagogical clarity, enabling Indonesian readers to grasp complex grammatical and phonetic concepts. Although the study focuses only on a limited portion of the text, it contributes to the broader understanding of religious text translation and suggests the need for further research to explore the application of these techniques across other sections of Tuhfatul Athfal.